Central Europe between the Great Powers: contemporary foreign-policy orientation - Ušiak Jaroslav (Sciendo, 2021)
The main aim of this this study was to highlight the relations between the Central European countries (Slovakia, Czechia, Poland and Hungary) and the two great powers—the United States and the Russian Federation. We examined the importance of this region from a geopolitical perspective, analysing the relations between the Central European countries and the great powers through two of their critical manifestations: military bases and energy security. The selection of these themes was justified by the frequent centralisation of the abovementioned topics in political discussions and their role in underpinning the securitisation of political leaders. The analysis of government strategy papers, and politicians’ statements and press releases, which included the views of three international relations experts, revealed diverse interstate relations. Each of the four Central European countries claims to be a responsible and reliable member of the North Atlantic Treaty Organization; however, not all of them place the same emphasis on this partnership. Regarding the energy sector, we came to the same conclusion. The countries declare their independence, but the RF continues to have a significant or dominant influence. The geographical position of the four surveyed countries is probably an important factor in this situation and the great powers generally adapt their foreign policy towards them accordingly, as evidenced by the selected topics. The results of the analyses confirmed the importance of this region from a geopolitical perspective.